Are first-generation cephalosporins obsolete? A retrospective, non-inferiority, cohort study comparing empirical therapy with cefazolin versus ceftriaxone for acute pyelonephritis in hospitalized patients. (16th March 2016) - Hobbs, Athena L. V.; Shea, Katherine M.; Daley, Mitchell J.; Huth, R. Gordon; Jaso, Theresa C.; Bissett, Jack; Hemmige, Vagish
Abstract: Objectives: Literature is lacking regarding the utilization of first-generation cephalosporins for the treatment of acute pyelonephritis. The aim of this study was to determine whether cefazolin is non-inferior to ceftriaxone for the empirical treatment of acute pyelonephritis in hospitalized patients. The primary outcome included a composite of symptomatic resolution plus either defervescence at 72 h or normalization of serum white blood cell count at 72 h (non-inferiority margin 15%). Secondary outcomes included length of stay and 30 day readmission. A subgroup analysis of the composite outcome was also conducted for imaging-confirmed pyelonephritis. Methods: This was a retrospective, non-inferiority, multicentre, cohort study comparing cefazolin versus ceftriaxone for the empirical treatment of acute pyelonephritis in hospitalized patients. Results: Overall, 184 patients received one of the two treatments between July 2009 and March 2015. The composite outcome was achieved in 80/92 (87.0%) in the cefazolin group versus 79/92 (85.9%) in the ceftriaxone group (absolute difference 1.1%, 95% CI −11.1% to 8.9%, P  = 0.83), meeting the pre-defined criteria for non-inferiority. The composite outcome for patients with imaging-confirmed pyelonephritis was achieved in 46/56 (82.1%) versus 42/50 (84.0%) for the cefazolin group and the ceftriaxone group, respectively (absolute difference 1.9%, 95% CI −12.8% to 16.5%, P  = 0.80). Additionally, there were no statistically significant differences in length of stay or 30 day readmission for cystitis or pyelonephritis. Conclusions: Cefazolin was non-inferior to ceftriaxone with regard to clinical response for the treatment of hospitalized patients with acute pyelonephritis in this study. No difference was observed for length of stay or 30 day readmission.